SISTEM INFORMASI EXPEDISI PENGIRIMAN BARANG PADA BAGIAN DISTRIBUSI PT. TEMPO BANDA ACEH - Ikram, M (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The purpose of this research is to find out and design a Freight Forwarding Expedition Information System at the Distribution Section of PT. Tempo Banda Aceh with HTML, PHP, CSS, JSON, AJAX and MySQL programming languages as database support. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. While in software development using the Agile method. From the results of the study it can be concluded that the information system for shipping freight forwarders at PT. Tempo Banda Aceh has followed the procedure using HTML, PHP, CSS, JSON, AJAX and MySQL programming languages as database support.